Manajemen Peningkatan Mutu Akademik di SD Negeri Bulusari 02 Kecamatan Bulakamba Kabupaten Brebes - Tasirun, Tasirun; Wuryandini, Endang; Rasiman, Rasiman (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Academic Quality Improvement Management is very important for every activity of an educational institution to achieve the desired goals. Improved Academic Quality Improvement Management can be seen from planning, organizing, implementing and supervising. The objectives of this research: (1) Describe and analyze planning for improving Academic Quality Improvement Management. (2) Describe and analyze the organization of improving Academic Quality Improvement Management. (3) Describe and analyze the implementation of Academic Quality Improvement Management improvements. (4) Describe and analyze the supervision of improving Academic Quality Improvement Management at SD Negeri Bulusari 02. The research approach used is qualitative. Qualitative research design goes through three stages, namely: orientation, focused exploration, and data analysis. Data collection techniques are interviews, observation sheets and documentation. This research uses triangulation techniques. Data analysis in three steps: condensing data, presenting data, and drawing conclusions. The research results show that: 1) Planning through planning procedures for improving Academic Quality Improvement Management includes formulating plans, setting targets, estimating needs, formulating policies, formulating budgeting and evaluating plans. 2) Organizing through procedures including programs for determining organizational structure and curriculum as well as workforce. 3) Implementation by analyzing the implementation of new student admissions (PPDB), implementation of teaching and learning activities (KBM), curriculum management and management of facilities and infrastructure. 4) The process of monitoring Academic Quality Improvement Management has stages, namely using assessment instruments, recording assessments and evaluations and carrying out follow-up actions. Conclusion Management of Academic Quality Improvement at SD Negeri Bulusari 02, Bulakamba District, Brebes Regency has been carried out through four activity steps, namely, planning, organizing, implementing, supervising. The author suggests that school principals can strive to improve the quality of Academic Quality Improvement Management by improving school management